2020
DOI: 10.1111/puar.13285
|View full text |Cite
|
Sign up to set email alerts
|

Civil Rights, Social Equity, and Census 2020

Abstract: This article examines Census 2020 relative to civil rights and social equity. Mandated by the U.S. Constitution, the Census is directly related to civil rights as Census totals are used to determine voting representation, and results impact billions of dollars of federal, state, and local funding across multiple areas including education, health care, and housing. Census undercounts impact marginalized communities, and this is a heightened concern for Census 2020 along two core social equity dimensions: (1) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…These subjective design choices resulted in "objective" data that helped entrench systemic racism in US society. To this day, aspects of the current Census' design result in "objective" data that adversely impact racialized groups (e.g., prison gerrymandering 125 , debate over adding a citizenship question 7 ).…”
Section: Subjectivity and Advocacy In Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…These subjective design choices resulted in "objective" data that helped entrench systemic racism in US society. To this day, aspects of the current Census' design result in "objective" data that adversely impact racialized groups (e.g., prison gerrymandering 125 , debate over adding a citizenship question 7 ).…”
Section: Subjectivity and Advocacy In Sciencementioning
confidence: 99%
“…Racism-related stress is multidimensional and differs from other forms of stress. It includes: [1] racism-related life events (i.e., salient racist acts that an individual has experienced), [2] racism microaggressions (i.e., insidious racist acts that occur on a more frequent basis), [3] vicarious racism (i.e., the observation of racist events impacting members of one's racialized group; e.g., a Black child observing police brutality against a Black adult), [4] collective experiences of racism (i.e., knowledge of racist events that happened to members of one's racialized group; e.g., Japanese internment camps in the US), [5] intergenerational trauma (i.e., emotional and behavioral responses to a traumatic event among the descendants of an individual who experienced the event), [6] social role demands and the need to adapt to White or dominant group society, and [7] structural/institutional racism's impact on living conditions, access to resources, and opportunities 66 . Finally, unlike other forms of stress, the impact of racism-related stress occurs across the lifespan.…”
Section: Indicators On Pain Physiologymentioning
confidence: 99%
“…According to the Society for Neuroscience, 23% of students enrolling in neuroscience Ph.D. programs and 14% of Ph.D. awardees in 2016/2017 were students from underrepresented backgrounds and 15% of postdoctoral trainees and 8% of program faculty identified with underrepresented backgrounds (Society for Neuroscience, 2017 ). Given that the 2020 US Census reported that 42.1% of the US population identifies as coming from an underrepresented backgrounds (Berry-James et al, 2020 ), these statistics indicate that there is an unmet need for innovative programs that foster recruitment and retention of URMs and/or disabled students in the neuroscience workforce, in order to better reflect the broader population that neuroscience research seeks to benefit.…”
Section: Leveraging the “Community First” Engagement Infrastructure T...mentioning
confidence: 99%
“…He finds that bureaucrats’ welfare policy discourse marginalized vulnerable populations, particularly African American women. To round out the symposium, Berry‐James, Gooden, and Johnson III (2020) examine the implementation of Census 2020; as Census undercounts disproportionately impact marginalized communities, there is heightened concern for Census 2020 regarding two core social equity dimensions: (1) race and ethnicity and (2) immigration and citizenship.…”
mentioning
confidence: 99%